WORLD SUMMIT ON SUSTAINABLE BEVELOPMENT 2002 DAN PEMBANGUNAN BERKELANJUTAN DI INDONESIA - Widhiyoga, Ganjar (Transformasi, 2010)
AbstractThe main concerns about international agreement is whether the corresponding parties will adhere the agreement or will waive it away, sometimes by excuse of an escape clause. Thus,it is important to dissect the agreemenet to World Summit on Sustainable Development 2002 since it became a major step for Indonesia to launch a sustainable development program.Keywords : sustainable development, legalization